RNA-seq analysis reveals genes related to photosynthetic carbon partitioning and lipid production in Phaeodactylum tricornutum under alkaline conditions - Liu, Jian; Yin, Weihua; Zhang, Xinya; Xie, Xuan; Dong, Guanghui; Lu, Yao; Tao, Baoxiang; Gong, Qiangbin; Chen, Xinyan; Shi, Chao; Qin, Yuan; Zeng, Rensen; et al. (Frontiers in Microbiology, 2022)
Alkaline pH can induce triacylglyceride accumulation in microalgae, however its molecular mechanism remain elusive. Here, we investigated the effect of 2-[N-cyclohexylamino]-ethane-sulfonic acid (CHES) -induced intracellular alkalization on the lipid production in Phaeodactylum tricornutum. Intracellular pH was increased upon CHES treatment, displaying a high BCECF fluorescence ratio. CHES significantly induced lipid accumulation but had no change in cell density and biomass. The expression of genes involved in photoreaction, carbon fixation, glycolysis, pentose phosphate pathway, amino acid catabolism, GS/GOGAT cycle, TCA cycle, triacylglyceride assembly, de novo fatty acid synthesis were up-regulated, while that in amino acid biosynthesis were down-regulated under CHES conditions. Correspondingly, the activity of phosphoribulokinase, carbonic anhydrase, pyruvate dehydrogenase and acetaldehyde dehydrogenase were enhanced by CHES treatment. Chloroplast-specific biological processes were activated by CHES treatment in P. tricornutum, which redirects the flux of carbon into lipid biosynthesis, meanwhile upregulates the expression of genes involved in de novo fatty acid biosynthesis, resulting in lipid accumulation under CHES conditions. These indicate an enhancement of intermediate metabolism, resulting in lipid accumulation by CHES.